Knowledge management model and instrument for implementation and adoption; perspective of developing country - Md. Idris, Kamil; Ali, K.N.; Aliagha, G. U. (Macrothink Institute, 2015)
This paper presents a KM model that comprises a set of KM hypothesis model and measurement models for understanding and implementation. Research uses 323 questionnaire surveys. A hypothesized model of KM process was tested using structural equation modelling approach with a proposed model and the instrument was therefore developed. Analysis of the five constructs of knowledge acquisition, creation, sharing, storage and dissemination with their reliability and Cronbach’s Alpha coefficient of 0.80, 0.71, 0.82, 0.87 and 0.87 respectively were used. Likewise, all fit indices and factor loadings were significant leading to a frugal model achievement. The study serves as a guide to KM for the construction organization implementation.